Densification: Globalised tourism shaping urban development and realities of local culture - Jonescu, Emil (2016)
Driven by tourism, the built environment that comprises many globalised cities increasingly reflects shifts in priority of economy over culture that manifests in the indistinct characteristics of its architecture. This paper provides commentary on development inevitability, and resultant densification and deterioration of culture and social fabric of globalised cities that focus on tourism through planning of urban precincts and the architecture that forms it, but not to the degree that it includes iconic architecture. Through critical analysis of Australian and international patterns of change in tourism, architecture, and urban design, and through critical visual analysis of South East Asian examples undertaken as part of an architectural research tour, this paper highlights that when leveraging off cultural difference, built up environments provide opportunities that can shape and drive tourism, providing a tourism experience product while perpetuating continuity of traditional behaviours, customs, and architecture. In support, this paper further provides a critique on density, globalisation, and consumer-centric architecture and urban design decisions that create environments with spatial realities that shape the behaviour of its occupants. The cities discussed form part of an architectural study tour and serve to demonstrate how two geographically related locations have strikingly divergent approaches to investing in the "currency" of experience of its tourists and inhabitants. Furthermore, the two South East Asian examples discussed provide a theoretical lens by which to apply an understanding of the future disadvantage and opportunity that await other neighbouring cities in the Asia-Pacific region that are yet to densify and capitalise on tourism potential, natural environment, culture, history, and architecture such as Perth, Western Australia.